Hydrodynamics and sediment transport in an estuary with an abrupt depth step - Pereyra, Mariana Gisele (2014)
The hydrodynamic patterns resulting from the combination of tide flow, riverine discharge and bathymetry and their effects on water circulation and sediment transport are studied to assess the impact of geomorphic changes in the Quequén Grande River estuary (Buenos Aires, Argentina). A depth step located at about 2 km from the sea, created by dredging to provide favourable navigational conditions in the harbour, induces different flow patterns in the deeper and shallow estuarine parts, creating an attractive system to study. The main purpose of this paper is to report key physical features of this water system and the results of detailed longitudinal and transverse measurements of velocity and backscatter intensity. The data reveal the selective settling of suspended sediments in the harbour and a net loss of sediments to the sea. The effects of local severe storms that cause an intense tidal intrusion and mixing as well as a stronger ebb flow and seiches are also described.